Asymmetric Hysteresis Loops in Co Thin Films - Ehrmann, Andrea; Blachowicz, Tomasz (Condensed Matter)
Asymmetric magnetic hysteresis loops are usually found in exchange bias (EB) systems, typically after field cooling a system below the Néel temperature of an antiferromagnet exchange coupled to a ferromagnet. Alternatively, asymmetric hysteresis loops may occur due to undetected minor loops or in systems with a rotational anisotropy. Here, we report on an exchange bias thin film system MgO(100)/Co/CoO, examined at room temperature, which is far above the blocking temperature, by the magneto-optical Kerr effect (MOKE). While the longitudinal hysteresis loops partly show steps which are well-known from diverse purely ferromagnetic systems, the transverse hysteresis loops exhibit clear asymmetries, similar to exchange biased systems at low temperatures, and unusual transverse magnetization values at saturation. Since minor loops and a rotational anisotropy can be excluded in this case, this asymmetry can possibly be a residue of the exchange bias coupling at lower temperatures.
Keywords: exchange bias; rotatable anisotropy; blocking temperature; minor loops; Co/CoO